The painful scrotum: An ultrasonographical approach to diagnosis - Malai Muttarak (2018)
Many disease processes, including inflammation, testicular torsion, testicular trauma, and testicular cancer, may have a similar clinical presentation as a painful scrotum. Differentiation of these disease processes is important for proper management. High-resolution ultrasonography (US) combined with colour Doppler ultrasonography (CDUS) is the imaging modality of choice in evaluating these patients. Gray-scale US helps to better characterise scrotal lesions. CDUS demonstrates testicular perfusion which aids in reaching a specific diagnosis. This pictorial essay is intended to review the causes, US appearances of disease processes causing the painful scrotum, and examination pitfalls of scrotal US.